2021
DOI: 10.3390/polym13050677
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanocarrier Entrapping Hydrophilic Drugs as Advanced Polymeric System for Dual Pharmaceutical and Cosmeceutical Application: A Comprehensive Analysis Using Box-Behnken Design

Abstract: The objective of the present research is to propose chitosan as a nanocarrier for caffeine—a commonly used drug in combating cellulite. Being a hydrophilic drug, caffeine suffers from insufficient topical penetration upon application on the skin. Chitosan nanoparticles loaded with caffeine were prepared via the ionic gelation technique and optimized according to a Box–Behnken design. The effect of (A) chitosan concentration, (B) chitosan solution pH, and (C) chitosan to sodium tripolyphosphate mass ratio on (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Thus, the interactions between protonated caffeine and positively charged deacetylated chitin groups lead to repulsion due to similar charges. Similar behavior was reported for nanocarriers of chitosan where a caffeine entrapment efficiency of 17.25 ± 1.48% was observed [44].…”
Section: Loading Na51* Hydrogels With Caffeinesupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the interactions between protonated caffeine and positively charged deacetylated chitin groups lead to repulsion due to similar charges. Similar behavior was reported for nanocarriers of chitosan where a caffeine entrapment efficiency of 17.25 ± 1.48% was observed [44].…”
Section: Loading Na51* Hydrogels With Caffeinesupporting
confidence: 83%
“…Thus, the interactions between protonated caffeine and positively charged deacetylated chitin groups lead to repulsion due to similar charges. Similar behavior was reported for nanocarriers of chitosan where a caffeine entrapment efficiency of 17.25 ± 1.48% was observed [44]. The entrapment efficiency of caffeine in the Na5 1 * hydrogels was found to be 5.82 ± 0.89%, with caffeine representing 1.02 ± 0.03% of the total weight of the hydrogel.…”
Section: Loading Na51* Hydrogels With Caffeinesupporting
confidence: 82%
“…These findings were consistent with Rampino et al and Konecsni et al (Konecsni et al, 2012 ; Rampino et al, 2013 ). It can be inferred that CS molecules at the mass ratio 2:1 were almost fully cross-linked and the excess TPP led to cross-linking between monodispersed particles into aggregates, resulting in larger particle size (Abosabaa et al, 2021 ). Increased PS could also be attributed to the accompanied increased in EE%.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that increasing the concentration of chitosan had a positive effect on the insecticide EE%. Previous studies have shown that increasing the chitosan concentration and chain length could increase the possibility of drug and insecticide entrapment in the polymer network and is directly related to drug and insecticide loading [19][20][21]. The electrical charge of the prepared nanoparticles depends on the concentration of chitosan.…”
Section: Discussionmentioning
confidence: 99%